1999
DOI: 10.1021/la980948v
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Flux through Micro- and Nanostructured Composites

Abstract: Nano-and microstructured materials differ from bulk materials because they are heterogeneous matrixes with large internal surface area. Interfaces inside nano-and microstructured composites can impact flux of probes through the matrix through unique interfacial chemistry and structure, interfacial binding and repulsion, and interfacial gradients. Gradients in properties are established at the interface between immiscible components; gradients generate forces which can drive flux. In microstructured composites,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Nanocomposites refer to heterogeneous nanostructured materials containing a large internal surface area as compared to the bulk homogeneous material [2]. Dispersing nanometer-size particles throughout the polymer electrolyte is one commonly used method of making such materials [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Nanocomposites refer to heterogeneous nanostructured materials containing a large internal surface area as compared to the bulk homogeneous material [2]. Dispersing nanometer-size particles throughout the polymer electrolyte is one commonly used method of making such materials [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Composite modified electrodes have been composed of a variety of materials, including polystyrene bead/ion exchange polymer composites, neutron-etched polycarbonate filter/ion exchange polymer composites, conducting polymer/ion exchange polymer composites, , sol−gel/ion exchange polymer composites, , and other polymer/polymer composites. Modifying electrodes with composites has been used to increase the mass transport through a modifying layer and to increase the physical stability and optical characteristics of the modifying layer . Recently, it has been shown that composite films can also alter the electrochemical selectivity of the electrode …”
Section: Introductionmentioning
confidence: 99%
“…In recent years, researchers have started modifying electrodes with composite films. Composite modified electrodes have been composed of a variety of materials, including polystyrene bead/ion exchange polymer composites, neutron etched polycarbonate filter/ion exchange polymer composites,conducting polymer/ion exchange polymer composites, , sol−gel/ion exchange polymer composites, , and other polymer/polymer composites. Modifying electrodes with composites has been used to increase the mass transport through a modifying layer and to increase the physical stability and optical characteristics of the modifying layer . Up until now, composite modified electrodes have been used to increase electrochemical flux.…”
Section: Introductionmentioning
confidence: 99%